Virtual Reality Tour Sebagai Media Promosi Dan Pembelajaran Alur Pelayanan Rumah Sakit - Dewi, Tika Sari (Jurnal Sistem Informasi Kesehatan Masyarakat, 2023)
Background: The Budi Rahayu Regional General Hospital Magelang is a hospital that has only been established for 2 years, so information technology is needed that supports promotion and provides information related to service flow. Virtual Reality Tour has been considered as a very effective technology that is useful as a media for promotion and learning related to hospitals which is more interesting because it provides a real/immersive and interactive experience to users.Methods: Using the Multimedia Development Life Cycle (MDLC) with 6 stages of multimedia development (concept, design, material collection, assembly, testing, distribution). Results: This research produces a website-based virtual reality tour. After that, user experience testing was carried out with benchmark results in the good category and positive impression values.Conclusion: Virtual reality tour can be used as a media for promotion and education of service flow in hospitals. The user experience in using virtual reality tours is that users feel they are in their original/immersive environment, can explore navigation freely so as to create interactive, practical learning, and create a feeling of security and comfort.Keywords: virtual reality tour, multimedia development life cycle, promotion of hospital service flow